Determination of Conduction and Valence Band Electronic Structure of LaTiOxNy Thin Film. Issue 9 (18th April 2017) - Pichler, Markus; Szlachetko, Jakub; Castelli, Ivano E.; Marzari, Nicola; Döbeli, Max; Wokaun, Alexander; Pergolesi, Daniele; Lippert, Thomas
Abstract: The nitrogen substitution into the oxygen sites of several oxide materials leads to a reduction of the band gap to the visible‐light energy range, which makes these oxynitride semiconductors potential photocatalysts for efficient solar water splitting. Oxynitrides typically show a different crystal structure compared to the pristine oxide material. As the band gap is correlated to both the chemical composition and the crystal structure, it is not trivial to distinguish which modifications of the electronic structure induced by the nitrogen substitution are related to compositional and/or structural effects. Here, X‐ray emission and absorption spectroscopy are used to investigate the electronic structures of orthorhombic perovskite LaTiO x N y thin films in comparison with films of the pristine oxide LaTiO x with similar orthorhombic structure and cationic oxidation state. Experiment and theory show the expected upward shift in energy of the valence band maximum that reduces the band gap as a consequence of the nitrogen incorporation. This study also shows that the conduction band minimum, typically considered almost unaffected by nitrogen substitution, undergoes a significant downward shift in energy. For a rational design of oxynitride photocatalysts, the observed changes of both the unoccupied and occupied electronic states have to be taken into account to justify the total band‐gap narrowing induced by the nitrogen incorporation. Abstract : N into O : Artificial photosynthesis using oxynitride semiconductors requires a good matching of the band gap to the solar spectrum. By comparing the electronic structure of isostructural LaTiO z and LaTiO x N y we show that the effect of the N substitution into the O sites affects not only the valence band maximum but also significantly shifts downward the energy of the conduction band minimum.